MORPHOLOGICAL STUDIES ON THE EFFECT OFNIGELLA SATIVA SEEDS ON THE MAMMARY GLAND OF MATURE MALE NORWAY RAT (Baghdad Science Journal, 2009)
Nigella sativa seeds (NSS) are reputed traditionally and scientifically as a potent agent that promote milk secretion (galactagogue), but their mechanism of action is studied trivially. One suggestion was that these seeds are bio-transformed to sex hormones within the ovaries. Therefore, this investigation was designated to throw light on the action of these seeds in the absence of ovaries i.e. in male rats. Thirty Norway male albino rats were used in this investigation. They were divided into experimental (n=20,fed NSS 2g/ Kg body weight /day for 14 days) and control (n=10, fed placebo for 14 days). After sacrifice mammary gland and blood samples were obtained. Experimental rats revealed a significant increase (p (0.01>in weight, hypertrophied mammary gland lobules with dilated ducts and rise in serum prolactin level, as compared to the controls. The Mammogenic action of NSS is most probably conveyed via extra-ovarian pathway. Nigella sativa seeds have an estrogen and progesterone like action or their steroidal saponins may be biotransformed to these hormones and cause mammogenesis .